PTH-082 Dysregulated polyamines in the inflammatory bowel disease gut – a novel therapeutic target. (17th June 2017) - Bailey, J
Abstract : Introduction: Polyamines (spermidine and spermine) are amino acid derivatives, critical for the maintenance of intestinal mucosal integrity, regulating inflammation and promoting mucosal healing. Levels of polyamines have been shown to be dysregulated in inflammatory bowel disease (IBD) patients; in chronic intestinal inflammation levels of spermine are reduced whereas spermidine is overexpressed. The individual role of each of these polyamines in the IBD gut is not known and so the consequences of this dysregulation are unclear. Method: Caco-2 adenocarcinoma colon epithelial cells were used to investigate the effect of spermidine and spermine on cell death and proliferation in vitro . Cells were infected with E. coli and treated with 10 µg/ml spermidine or 30 µg/ml spermine for 24 hours. Alongside this, cells were treated with 250 µM trans -4-methylcyclohexylamine (4MCHA) for 8 days to deplete endogenous spermidine prior to infection. Supernatants were used to determine the cytotoxic effect of E. coli in the presence or absence of polyamines by quantifying lactate dehydrogenase (LDH) release. Cell proliferation was assessed by BrdU incorporation and cell cycle analysis of propidium iodide stained cells by flow cytometry. Data were assessed for normality and analysed by one-way ANOVA with a Tukey post-hoc test. Results: Addition of exogenous spermine significantly reduced infection-induced apoptosis of intestinal epithelial cells. The number of proliferating epithelial cells was significantly increased in cultures which had been depleted of spermidine prior to infection when compared to cells which had been infected but retained endogenous spermidine. This was reversed by the addition of exogenous spermidine; the proportion of cells in G1 phase was reduced and cells accumulated in S phase, indicating a reduction in proliferation as cells were unable to progress through to G2 phase. Conclusion: In the absence of spermidine, infected intestinal epithelial cells increased proliferation to remove infected cells and clear the infection. Exogenous spermidine supressed this proliferation. In the IBD gut, levels of spermidine are increased; I hypothesise that overexpression of spermidine blocks renewal of the epithelium during chronic inflammation. Additionally, spermine reduced apoptosis of intestinal epithelial cells but, since IBD patients have a spermine deficiency in the gut, levels of epithelial cell apoptosis will be increased. I suggest that the effect of dysregulated polyamines in the IBD gut is twofold: overexpression of spermidine prevents proliferation of epithelial cells to renew the epithelium following damage due to inflammation and a lack of spermine increases apoptosis, further exacerbating the loss of epithelial cells and, thus, loss of a competent barrier. Redressing this balance could reduce inflammation and allow mucosal healing. Disclosure of Interest: None Declared